Evolution, Monitoring and Predicting Models of Rockburst Precursor Information for Rock Failure - Wang, Chunlai (Springer Singapore, 2018)
This open access book focuses on investigating predicting precursor information and key points of rockburst in mining engineering through laboratory experiment, theoretical analysis, numerical simulation and case studies. Understanding the evolution patterns for the microstructure instability of rock is a prerequisite for rockburst prediction. The book provides a guide for readers seeking to understand the evolution patterns for the microstrucure of rock failure, the predicting key point of rock failure and the rockburst predicting model. It will be an essential reference to understand mechanism of rockburst and sheds new light on dynamic disasters prediction. Chapters are carefully developed to cover (1) The evolution patterns for the microstructure instability of rock; (2) Rockburst hazard monitoring and predicting criterion and predicting models. The book addresses the issue with a holistic and systematic approach that investigates the occurrence mechanism of rockburst based on the evolution patterns for the microstructure of rock failure and establishes the predicting model of rockburst. This book will be of interest to researchers of mining engineering, rock mechanics engineering and safety engineering.